Diet-related knowledge, attitudes, and behaviors among young and middle-aged individuals with high-normal blood pressure: A cross-sectional study in China - Mu, Tingyu; Xu, Rixiang; Zhu, Qianyin; Chen, Lingshan; Dong, Die; Xu, Jiayi; Shen, Cuizhen (Frontiers in Public Health, 2022)
Abstract Background: Dietary modifications play an important role in the prevention and management of high-normal blood pressure. The aim of this study was to investigate diet-related knowledge, attitudes and behaviours, and the socio-demographic determinants of these, among young and middle-aged Chinese individuals with high-normal blood pressure. Methods: Data from the 2015 China Health and Nutrition Survey (CHNS) were analysed in this study. In total, 1756 subjects with high-normal blood pressure were included. Chi-square test and binary logistic regression analysis were conducted to identify risk factors toward diet-related knowledge, attitudes and behaviours. Results: 37.4% of the participants knew about the Chinese Food Pagoda (CFP) or the Dietary Guidelines for Chinese Residents (DGCR). Overall, 39.8% of the subjects were classified as having adequate diet-related knowledge literacy, 27.8% reported positive diet-related attitudes to healthy eating, and 35.3% reportedly looked for nutrition knowledge. 72.4% and 80.1% of the participants reported liking to eat fruits and vegetables, respectively. Individuals with a middle school education (OR = 1.784, 95% CI = 1.236-2.576), high school/vocational education (OR = 1.944, 95% CI = 1.305-2.896), college degree or above (OR = 2.089, 95% CI = 1.341-3.322), who were living in a rural area (OR =1.311, 95% CI =1.048-1.639), proactively looking for nutrition knowledge (OR =1.529, 95% CI = 1.227-1.906), and reported liking to eat vegetables (OR =1.939, 95% CI =1.409-2.688) were more likely to have sufficient dietary knowledge literacy. Managers (OR =1.655, 95% CI = 1.039-2.635) were more likely to have positive dietary attitudes. Female gender (OR =1.396, 95% CI = 1.089-1.790), high school/vocational school education (OR =2.071, 95% CI =1.269-3.379), college degree and above (OR =2.207, 95% CI = 1.262-3.862), knowledge about the CFP or DGCR (OR =8.138, 95% CI = 6.326-10.468), and sufficient dietary knowledge literacy (OR =1.338, 95% CI = 1.050-1.705) were associated with an increased likelihood of looking for nutrition knowledge. Conclusions: Groups with males, living in rural, lower education, farmer, worker, service worker, and work in the non-government employed unit may have poor diet-related knowledge, attitudes, behaviours in people with high-normal blood pressure.